Association between body size and atrial myopathy: Investigation using the prevalence of left atrial low-voltage areas - Yasuhiro Matsuda; Masaharu Masuda; Hiroyuki Uematsu; Ayako Sugino; Hirotaka Ooka; Satoshi Kudo; Subaru Fujii; Mitsutoshi Asai; Shin Okamoto; Takayuki Ishihara; Kiyonori Nanto; Takuya Tsujimura; et al. (Heliyon)
Background: Left atrial low-voltage areas (LVAs) are known to be associated with atrial myopathy and atrial fibrillation (AF) recurrence after catheter ablation. However, the association between body size and prevalence of LVAs has not been fully elucidated. The purpose of this study was to clarify the association between body size and the prevalence of LVAs in patients with AF ablation. Methods: In total, 1,479 (age, 68 ± 10 years; female, 500 [34 %]) consecutive patients who underwent initial AF ablation were enrolled. Body mass index (BMI), height and body weight were used as indicators of body size. BMI was divided into four groups, namely <18.5 kg/m2, 18.5–25.0 kg/m2, 25.0–30.0 kg/m2, ≥30.0 kg/m2. LVAs were defined as areas with bipolar voltage of <0.5 mV covering ≥5 cm2 of left atrium. Rhythm outcome following the catheter ablation procedure was followed for 24 months. Results: LVAs were found in 349 (24 %) patients. A J-curve phenomenon was found between BMI or body weight and the prevalence of LVAs. In particular, BMI <18.5 kg/m2 was an independent predictor of LVAs (odds ratio, 1.9; 95 % confidence interval: 1.01–3.5; p = 0.046). Conversely, the prevalence of LVAs increased with decreasing height. For rhythm outcome, there was a significant difference in freedom from AF recurrence among groups stratified by BMI (p = 0.001). Conclusions: A J-curve phenomenon existed between BMI or body weight and the prevalence of LVAs, which reflects atrial myopathy, in patients with AF ablation. In contrast, the prevalence of LVAs increased with decreasing height.